The aging surgeon: mandatory annual competency testing for surgeons aged 65 and older - Bloemink, Anita Justine (My University, 2021)
In South Africa, there is currently no law which dictates when surgeons should ‘put down their scalpel’. A self-evaluation of skills is considered a reliable measure of the surgeon’s capabilities, allowing surgeons who work in private practice to retire when they deem themselves no longer fit to practise. The typical retirement age of 65 correlates with the onset of a decline in certain cognitive capacities and fine motor skills that are necessary for the practise of surgery, and this therefore poses a risk to patients if it is not monitored. The media continues to investigate and highlight cases where patients suffer damages, and occasionally death, at the hands of elderly surgeons. This research report aims to defend the thesis that there should be mandatory annual competency testing for surgeons aged 65 and older. I employed the typical research methods and standards applicable to philosophical research. This primarily involved the interpretation and critical analysis of salient texts and the posting and defence of new arguments. My critical analysis of relevant texts involved the definition and clarification of concepts, the identification and criticism of assumptions, the analysis and evaluation of theoretical frameworks, the development and defence of arguments, the use of counter-examples, and the articulation of the most plausible interpretation of significant concepts found in the sources. A critical analysis of the void in law relating to competency testing of surgeons has been conducted in light of moral theories, ethical principles and frameworks. Should elderly surgeons be deemed fit to operate following the competency testing, no accusations can be made regarding their abilities nor age-related deficits. This is in the best interest of both the surgeon and the patient. It is, therefore, an ethical and legal responsibility to legislate mandatory competency testing for surgeons who wish to continue operating at age 65 and beyond. Whilst ‘age’ and ‘competence’ are independent variables, no one should be discriminated against solely because of his/her age. Real life experience and exposure gained by the mature person is invaluable and should be fully utilised as long as the individual remains competent. This privilege should be extended to the currently over regulated professions such as airline pilots. In reality, tests will expose both competent 65 year olds and so too incompetent 65 year olds who are unfit to 3 practice. Let competence determine the right to continue one’s profession, and not age.
A research report submitted in partial fulfilment of the requirements for the degree Masters of Science in Medicine in Bioethics and Health Law to the Faculty of Health Sciences, School of Bioethics, University of the Witwatersrand, Johannesburg, 2021